Assessment of Aglycones Isoflavone Profiling of Staple Indian Grain Flours and Soybean Sprout-Flour - Raman MANOHARLAL; Saiprasad V.S. GANDRA (Notulae Scientia Biologicae, 2018)
In the present study, investigation of fourteen traditional and most commonly used Indian staple grain flour types (viz. wheat, white rice, processed little millet, maize, all-purpose/refined wheat flour, chickpea flour, toasted gram flour, little millet, quinoa, soybean, white millet, pearl millet, semolina/cream of wheat and finger millet) was undertaken for the assessment of 3 major bioactive aglycone forms of isoflavone (IF): daidzein (DI), glycitein (GY) and genistein (GN), with a special interest on the effect of sprouting on total and individual IF components. The obtained results showed that the content and composition of total IF were negligible among all the investigated flours except for soybean, wherein detectable total (227 mg kg-1) and individual IF (45, 129 and 53 mg kg-1 for DI, GY and GN respectively) components were observed. From soybean mature seeds to sprouts formation with ~80% germination rate at a pilot-scale, a 31% increase in total IF (298 mg kg-1), characterised by an individual and respective increment of 30% (58 mg kg-1), 25% (161 mg kg-1) and 48% (78 mg kg-1) in corresponding DI, GY and GN components, was observed. The current results demonstrated that for the Indian scenario, contribution of aforementioned grains, other than soybean in daily dietary intake of IF is negligible and sprouting represents an effective way to enhance the endogenous IF content.